Pharyngocutaneous Fistula and Horner's Syndrome following Loosening of Locking Screw of Anterior Cervical Plating: A Rare Case Report and Management - Jogani, Abhinav (Asian J Neurosurg, 2021)
We hereby present a rare case of pharyngocutaneous fistula associated with locking screw loosening causing internal cricopharynx perforation and Horner's syndrome following anterior cervical plating. A 27-year-old male patient had undergone anterior cervical plating at C5–C7 level due to gunshot injury to the neck, and 1 month postsurgery, he developed fistula in the neck showing discharge of consumed food contents. He presented to us 1 year postsurgery with the discharging fistula, left upper-limb weakness, and Horner's syndrome that developed after surgery. The previously unexplored right side was used to remove implant, and owing to solid union at corpectomy, no additional fixation was performed. Intraoperatively, pharyngeal wall dehiscence was observed. Attempt of removal of impinged screw was abandoned since it migrated into the esophagus. Serial abdomen radiographs revealed successive passage of screw through the gastrointestinal (GI) tract until it could not be visualized. As the patient showed reduced discharge, a GI surgeon gave a conservative trial with nasogastric intubation. Currently, fistula is showing minimal discharge with no food. Having knowledge of this possible rare outcome and awareness of various multidisciplinary approaches for management makes practicing spine surgeon equipped to handle such undesirable complications.